2016
DOI: 10.1002/oa.2523
|View full text |Cite
|
Sign up to set email alerts
|

Dama Dentition: A New Tooth Eruption and Wear Method for Assessing the Age of Fallow Deer (Dama dama)

Abstract: Reliable ageing techniques for wild animals are notoriously challenging to develop because of the scarcity of sizeable collections of known-age specimens. Without such techniques it is difficult to reconstruct hunting patterns, which is a significant problem for the examination of assemblages from pre-farming cultures. This paper presents a new method, based on mandibular tooth eruption and wear, for assessing the age of fallow deer. The method was developed from a large collection (n = 156) of known-age Dama … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Wherever possible 3 rd mandibular molars were collected; however, for three locations (France, Haifa and Turkey) only 1 st mandibular incisors were available (Table ). Fallow deer 1 st permanent incisors erupt at 7–8 months and the 3 rd molar at 15–26 months . We are aware that this may cause discrepancies in the data presented in this study as inter‐tooth variation has previously been noted in mammalian populations.…”
Section: Methodsmentioning
confidence: 81%
“…Wherever possible 3 rd mandibular molars were collected; however, for three locations (France, Haifa and Turkey) only 1 st mandibular incisors were available (Table ). Fallow deer 1 st permanent incisors erupt at 7–8 months and the 3 rd molar at 15–26 months . We are aware that this may cause discrepancies in the data presented in this study as inter‐tooth variation has previously been noted in mammalian populations.…”
Section: Methodsmentioning
confidence: 81%
“…Additional modern fallow deer bone was collected over the last 2 years and this cumulative data is reflected in this paper. Measurements of these remains were taken according to the standards of Von den Driesch (1976) and mandibular dental ageing was undertaken using the system set out by Bowen et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…The cementum annuli method is very accurate (Aitken, 1975; Baumgartner et al, 2004; De Bie, 1977; Miller, 1974a; Pérez‐Barbería et al, 2014) but destructive, time consuming (Brown & Chapman, 1990) and relatively expensive. Ageing methods based on dental wear and eruption patterns are relatively quick, non‐destructive and cheap and therefore often provide the largest datasets on animal mortality patterns available, including those for archaeological and modern Cervidae (e.g., Baumgartner et al, 2004; Bowen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tooth wear rates vary within and among populations, even change during an individual's lifetime, depending on diet, food availability, substrate, health, genetics and individual teeth's enamel mineralization characteristics (e.g., Hewison et al, 1999; Kojola et al, 1998; Miller, 1974b; Skogland, 1984; Skogland, 1988). Despite these limitations, several studies have shown that TWE is useful to estimate age‐at‐death for (archaeo)faunal populations (e.g., Lowe, 1967, in Grant, 1978, for red deer [ Cervus elaphus ]; Greenfield & Arnold, 2008, for sheep [ Ovis aries ] and goat [ Capra hircus ]; Payne, 1973, for sheep and goat; Høye, 2006, for roe deer; Bowen et al, 2016, for fallow deer [ Dama dama ]; Baumgartner et al, 2004, for red deer; Twiss, 2008).…”
Section: Introductionmentioning
confidence: 99%